Determination of cavities using electrical resistivity tomography - PUTIŠKA, René; NIKOLAJ, Maroš; DOSTÁL, Ivan; KUŠNIRÁK, David (Contributions to Geophysics and Geodesy, 2012)
Geophysical surveys for cavity detection are one of the most common nearsurface applications. The usage of resistivity methods is also very straightforward for the air-filled underground voids, which should have theoretically infinite resistivity in the ERT image. In the first part of the paper, we deal with the comparison of detectability of the cavity by several types of the electrode arrays, the second part discusses the effect of a thin layer around the cavity itself, by means of 2D modelling. The presence of this layer deforms the resistivity image significantly as the resistive anomaly could be turned into a conductive one, in the case when the thin layer is more conductive than the background environment. From the electrical array analysis for the model situation a dipole-dipole and combined pole-dipole shows the best results among the other involved electrical arrays.